Learning computer technology in the development of educational practice «Care for surgical patients» - Dyabkin E. V. (Interactive science, 2017)
this article deals with the problem of implementation in the educational process of new computer technologies. Modern students of medical educational institutions need computer programs, which encourage them to absorb necessary educational material and stimulate cognitive interest in the subject. This training flash program is recommended for implementation in the educational process in educational practice and it consists of «Care for surgical patients» module. The computer program includes educational material, revealing the structure and equipment of the surgical department with the use of animation clip. In order to check the quality of learning, the student must pass a test and solve situational problems. This article is devoted to the indicated problem.
Keywords: flash-программа; устройство хирургического отделения; flash program; the device of the surgical department